2022
DOI: 10.3389/fimmu.2022.860661
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223 as a Regulator and Therapeutic Target in Liver Diseases

Abstract: MicroRNAs (miRNAs) are endogenous non-coding single-stranded small molecule RNAs consisting of 20–24 nucleotides that are highly conserved in species evolution. Expression of miRNAs is strictly tissue-specific, and it is chronological in fungi and plants, as well as in animals. MiR-223 has been shown to play a key role in innate immunity, and dysregulation of its expression contributes to the pathogenesis of multiple inflammatory diseases, and cancers. In this article the biosynthesis and functions of miR-223 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…MiRNAs are crucial organismal adjustment factors which come into play biological function and take part in a mass of pathophysiological processes by complementary nucleotide sequence-speci c binding to the 3′-UTR of the downstream mRNA to restrain translation process of target gene [29]. Several studies have provided evidence that various miRNAs adjust the process of hepatic brosis, including miR-98-5p and miR-34a [30,31], but no direct evidence demonstrated that miR-330-3p regulate the process of hepatic brosis.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are crucial organismal adjustment factors which come into play biological function and take part in a mass of pathophysiological processes by complementary nucleotide sequence-speci c binding to the 3′-UTR of the downstream mRNA to restrain translation process of target gene [29]. Several studies have provided evidence that various miRNAs adjust the process of hepatic brosis, including miR-98-5p and miR-34a [30,31], but no direct evidence demonstrated that miR-330-3p regulate the process of hepatic brosis.…”
Section: Discussionmentioning
confidence: 99%
“…The organization is such that the activation of TLR9 up-regulates miR-223 by NF-kB binding on the promoter of miR-223 which further reduces TLR9/NF-kB- mediated inflammation by targeting IKKa expression (refer to Table 3 ). 74 75 76 77…”
Section: Methodsmentioning
confidence: 99%
“…promoter of miR-223 which further reduces TLR9/NF-kB-mediated inflammation by targeting IKKa expression(refer to Table 3) [74][75][76][77] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, genetic ablation of miR-223 exacerbates liver fibrosis in mice upon injury [ 15 , 16 ]. These results suggest miR-223 plays a protective role against fibrogenesis and could represent a new therapeutic target to combat with liver fibrosis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%